Evaluating Security Through Isolation and Defense in Depth - Bodden, Eric; Pottebaum, Jens; Fockel, Markus; Gräßler, Iris (IEEE Security & Privacy)
Keywords: Law; Electrical and Electronic Engineering; Computer Networks and Communications

Uncovering Impact of Innovation: Continuous Stakeholder Engagement through Scenario-based Systems Engineering - Pottebaum, Jens; Ebel, Marcel; Gräßler, Iris (Proceedings of the 21st ISCRAM Conference (ISCRAM 2024))
The importance of extreme weather situations is increasing due to their number and, above all, their impact on stakeholders in emergency response. They are characterized by cascading effects with global and local interdependencies. Extreme data must be included as a basis for decision-making. The impact in emergency response depends on diverse, multidisciplinary competencies required to interpret information. Scenarios are used in various forms of preparation: in exercises, but also for the design of information systems and validation. Based on literature, this article brings together different types of scenarios and related work in the field of Model-Based Systems Engineering. Using an exemplary case relating to possible pluvial urban floods, the added value resulting from a focus on the impact of innovative solutions is discussed. It is shown that the use of scenarios helps to make the desired impact assessable for decision-makers in all phases of research and development projects.

Methodology for Certification-Compliant Effect-Chain Modeling - Gräßler, Iris; Wiechel, Dominik; Koch, Anna-Sophie; Sturm, Tim; Markfelder, Thomas (Systems)
The success of engineering complex technical systems is determined by meeting customer requirements and institutional regulations. One example relevant to the automobile industry is the United Nations Economic Commission of Europe (UN ECE), which specifies the homologation of automobile series and requires proof of traceability. The required traceability can be achieved by modeling system artifacts and their relations in a consistent, seamless model—an effect-chain model. Currently, no in-depth methodology exists to support engineers in developing certification-compliant effect-chain models. For this purpose, a new methodology for certification-compliant effect-chain modeling was developed, which includes extensions of an existing method, suitable models, and tools to support engineers in the modeling process. For evaluation purposes, applicability is proven based on the experience of more than 300 workshops at an automotive OEM and an automotive supplier. The following case example is chosen to demonstrate applicability: the development of a window lifter that has to meet the demands of UN ECE Regulations R156 and R21. Results indicate multiple benefits in supporting engineers with the certification-compliant modeling of effect chains. Three benefits are goal-oriented modeling to reduce the necessary modeling capacity, increasing model quality by applying information quality criteria, and the potential to reduce costs through automatable effect-chain analyses for technical changes. Further, companies in the automotive and other industries will benefit from increased modeling capabilities that can be used for architecture modeling and to comply with other regulations such as ASPICE or ISO 26262.
Keywords: Information Systems and Management; Computer Networks and Communications; Modeling and Simulation; Control and Systems Engineering; Software

Resilient Requirements Engineering - Gräßler, Iris; Oleff, Christian; Preuß, Daniel; Koch, Anna-Sophie (Zeitschrift für wirtschaftlichen Fabrikbetrieb)
Entwicklungsprojekte stehen in einem Spannungsfeld von Volatilität, Unsicherheit, Komplexität und Ambiguität (VUCA). Resilient Requirements Engineering (RRE) ist ein vielversprechender Ansatz, diesen Rahmenbedingungen gerecht zu werden und erfolgreich zu entwickeln. Es werden Methoden aus den drei Innovationsfeldern des RRE – Vorausschau, Effizienz und Nachhaltigkeit – angewendet, um Effizienzpotenziale in der Produktentwicklung zu nutzen und frühzeitig Nachhaltigkeitsdimensionen in der Ermittlung von Stakeholderbedürfnissen zu verankern.
Keywords: Management Science and Operations Research; Strategy and Management; General Engineering

Automatisierte Abhängigkeitsanalyse von Anforderungen zur Wirkkettenmodellierung - Gräßler, Iris; Preuß, Daniel (Stuttgarter Symposium für Produktentwicklung SSP 2023)
Effect chain modelling is a method for creating information models for impact analyses of changes in system elements. For the estimation of change propagation, dependencies between requirements must be detected. The high number of require- ment dependencies in the engineering of complex technical systems results in the need for automation. In a study, it was shown that transformer models (BERT) are suitable for the automated dependency analysis of requirements. However, there are currently deficits in the applicability of the models for different projects without an extensive and heterogeneous training database. This paper investigates how active learning can be used to train BERT models (active-BERT) in order to increase the performance of the models for classifying requi- rement dependencies of projects with heterogeneous require- ments. The results show that the performance of the models increases significantly through active learning. Through active- BERT, engineers are enabled to model effect chains efficiently and to handle requirement changes effectively.

Customized impact analyses for technical engineering changes - Gräßler, Iris; Wiechel, Dominik (2023 18th Annual System of Systems Engineering Conference (SoSe))

Handling of uncertainties in the design of sustainable Additive Manufacturing products by merging Design-for-X and Scenario-Technique - Gräßler, Iris; Mozgova, Iryna; Pottebaum, Jens; Ott, Manuel; Jung, Philipp; Hesse, Philipp (Procedia CIRP ICME)
New technologies and materials carry significant potential for sustainable production and use of products. As an example, Additive Manufacturing technologies and materials promise lightweight design and energy efficient use of parts. Exhausting the full potential requires: a) consideration of uncertainties with respect to future capabilities, and b) upgradeable design guidelines to cover advancements consistently. The proposed approach merges concepts of Design-for-X with foresight algorithms of Scenario-Technique to derive actionable knowledge. It is validated by an application in the field of Additive Manufacturing, namely Metal Fused Deposition Modelling. Engineers benefit from the intuitive access to heterogeneous types of sustainability related information.
Keywords: Design-for-X; Scenario-Technique; sustainability; uncertainty; Life-Cycle Engineering; Additive Manufacturing; Circular Economy

Entwicklung zukunftsfähiger Geschäftsmodelle in der Automatisierungstechnik anhand von Megatrends - Gräßler, Iris; Tusek, Alena Marie; Özcan, Deniz (Automation 2023)

KI-basierte Extrahierung von Anforderungen aus Regularien für die Automobilentwicklung - Gräßler, Iris; Özcan, Deniz; Preuß, Daniel (Design fox X - Beiträge zum 34. DfX-Symposium)

Defense-in-Depth als neues Paradigma der sicherheitsgerechten Produktentwicklung: interdisziplinäre, bedrohungsbewusste und lösungsorientierte Security - Gräßler, Iris; Bodden, Eric; Wiechel, Dominik; Pottebaum, Jens (Konstruktion)
inhalt Der verlässliche Betrieb von technischen Produkten wird zunehmend durch bewusste Angriffe bedroht. Vollständige Sicherheit ist dabei nicht möglich, durchschlagende Angriffe sind unvermeidbar (Assume Breach). Dies erfordert einen Paradigmenwechsel in der sicherheitsgerechten Entwicklung mechatronischer und cyber-physischer Systeme hin zu Defense-in-Depth. Systeme müssen so ausgelegt werden, dass sie auch bei gezielten Angriffen möglichst hohe Zuverlässigkeit und Sicherheit gewährleisten. Der hier beschriebene Lösungsansatz erweitert das Systemmodell um Angriffsszenarien und Verteidigungslinien. Diese werden am Beispiel eines industriellen Schließsystems zur Anlagensicherheit erläutert. Entwickler werden sensibilisiert, Angriffe systematisch zu berücksichtigen und interdisziplinär Verteidigungselemente gegenüber Bedrohungen und Angriffen zu spezifizieren.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science; Theoretical Computer Science

Introduction—The Digital Twin of Humans - Gräßler, Iris; Steffen, Eckhard; Maier, Günter W.; Roesmann, Daniel (The Digital Twin of Humans)

The Digital Twin of Humans

Individual Assembly Guidance - Pöhler, Alexander; Gräßler, Iris (The Digital Twin of Humans)

Integration of Human Factors for Assembly Systems of the Future - Roesmann, Daniel; Gräßler, Iris (The Digital Twin of Humans)

POTENTIALS AND GOALS OF MODELS IN STRATEGIC PRODUCT PLANNING AND INNOVATION MANAGEMENT - Gräßler, Iris; Koch, Anna-Sophie; Tusek, Alena Marie (Proceedings of the Design Society)
Abstract New trends and technologies in product creation increase complexity, but at the same time create new potentials such as efficiency rise in task processing by Artificial Intelligence. Established models in the early phase of product creation such as the W-model or the Aachener Innovation Management model, do not fully exploit these new potentials in the field of strategic product planning and innovation management (SPPIM). For this reason, existing models are analysed in SPPIM in order to derive a requirements profile consisting of potentials and goals for a new model. A new model in SPPIM lays the foundation to support companies in enabling a more efficient task fulfilment by taking advantage of new technologies and trends. To guide the development of advanced SPPIM models, the derived potentials and goals are applied to the guideline VDI 2220:1980.

Interdependency study of design guidelines - Hesse, Philipp; Gräßler, Iris (Climate Protection, Resource Efficiency, and Sustainable Engineering: Transdisciplinary Approaches to Design and Manufacturing technology.)

Sustainable product life cycle - Hesse, Philipp; Gräßler, Iris (Climate Protection, Resource Efficiency, and Sustainable Engineering: Transdisciplinary Approaches to Design and Manufacturing technology.)

Begriffe der strategischen Produktplanung und -entwicklung. Produkt und hybride Leistung - Gräßler, Iris; Ovtcharova, Jivka; Dattner, Michael; Dietert, Tilko; Dietz, Patrick; Elstermann, Matthes; Fayet, Celestin; Hauck, Andreas; Häuser, Frank; Fischer, Holger; Herzog, Michael; Köhler, Christian; et al.

Creating Synthetic Training Data for Machine Vision Quality Gates - Gräßler, Iris; Hieb, Michael; Roesmann, Daniel; Unverzagt, Marc

Creating Synthetic Datasets for Deep Learning used in Machine Vision - Gräßler, Iris; Hieb, Michael

CONSIDERING ENGINEERING ACTIVITIES AND PRODUCT CHARACTERISTICS TO ACHIEVE MATERIAL CIRCULARITY BY DESIGN - Gräßler, Iris; Hesse, Philipp (Proceedings of the Design Society)
Abstract To select design guidelines engineers have to identify relevant from a bewildering amount of design guidelines. In this paper, a rule-based method for selecting design guidelines for material circularity selection is presented. For this purpose, a generic Product Life Cycle model is detailed with regard to Multi Material cycles (gPLC-MM). The presented method is divided into four steps. Core of the presented method is the comparison of circular product strategies with product life phases and material recovery processes. Engineering activities and increments of the product architecture are used to identify design guidelines. The results show that through the material circularity-oriented design guideline identification method, the product architecture is designed for different processes and technologies, to recover materials. The method allows engineers to select guidelines in a more targeted and consolidated way in sustainability-friendly product engineering.
Keywords: Sustainability; Circular economy; Conceptual design

Virtual Test Scenarios for Human-Centered Design with Virtual Measurement Systems - Gräßler, Iris; Roesmann, Daniel; Unverzagt, Marc; Pottebaum, Jens (Poster)
The involvement of human workers is an essential part of the design of production systems. In this context, test scenarios in Virtual Reality are increasingly used to verify the fulfillment of requirements. This paper proposes a procedure for generating virtual test scenarios. The objective is to support human- centered design by means of virtual measurement systems. The procedure involves three steps: selecting relevant human factors in requirements, modeling the virtual test scenario, and carrying out the verification study. The goal is to advance the significance of testing outputs.
Keywords: virtual reality; virtual measurement systems; virtual test scenario; human-centered design

Virtual learning environment for teaching the handling of collaborative robots - Gräßler, Iris; Hieb, Michael; Roesmann, Daniel; Unverzagt, Marc; Pottebaum, Jens (SSRN Electronic Journal)
Keywords: General Earth and Planetary Sciences; General Environmental Science

Cloud-Computing für die Verwendung synthetischer Trainingsdaten für Machine Vision Quality Gates - Gräßler, Iris; Hieb, Michael (Automation 2023)

Creating Synthetic Training Datasets for Inspection in Machine Vision Quality Gates in Manufacturing - Gräßler, Iris; Hieb, Michael (Lectures)
Manufacturing companies face the challenge of reaching required quality standards. Using optical sensors and deep learning might help. However, training deep learning algorithms require large amounts of visual training data. Using domain randomization to generate synthetic image data can alleviate this bottleneck. This paper presents the application of synthetic image training data for optical quality inspections using visual sensor technology. The results show synthetically generated training data are appropriate for visual quality inspections.
Keywords: synthetic training data; machine vision quality gates; deep learning; automated inspection and quality control; production control

Efficient Formalisation of Technical Requirements for Generative Engineering - Gräßler, Iris; Preuß, Daniel; Brandt, Lukas; Mohr, Michael (Proceedings of the Design Society)

Identification and prediction of standard times in machining for precision steel tubes through the usage of data analytics - Weller, Julian; Roesmann, Daniel; Eggert, Sönke; von Enzberg, Sebastian; Gräßler, Iris; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Human Factors in der integrierten Produktentwicklung - Gräßler, Iris; Roesmann, Daniel; Pottebaum, Jens (Zeitschrift für wirtschaftlichen Fabrikbetrieb)
In der zukünftigen Produktion werden der Aufbau und die Entwicklung der Fähigkeiten der Mitarbeiter:innen ein entscheidender Wettbewerbsvorteil von Unternehmen. In menschenzentrierten Montagesystemen passen sich die Mitarbeiter:innen auf der Grundlage von Lernprozessen an neue und sich ändernde Aufgaben an. Dazu muss der Bezug zu den Fähigkeiten der Mitarbeiter:innen im Zuge der integrierten Produkt-und Prozessentwicklung vorgesehen werden. Daher wurde eine Methodik entwickelt, die diese Fähigkeiten explizit abbildet und sie sowohl in der Entwicklung als auch in der kurzfristigen Personaleinsatzplanung bei der Aufgabenzuordnung berücksichtigt. Zur Anwendung wurde die Methodik prototypisch in einem Software-Werkzeug umgesetzt und in Kombination mit einer diskreten ereignisorientierten Simulation erprobt.
Keywords: Management Science and Operations Research; Strategy and Management; General Engineering

Re-Envisioning Industrial Control Systems Security by Considering Human Factors as a Core Element of Defense-in-Depth - Pottebaum, Jens; Rossel, Jost; Somorovsky, Juraj; Acar, Yasemin; Fahr, René; Arias Cabarcos, Patricia; Bodden, Eric; Gräßler, Iris (2023 IEEE European Symposium on Security and Privacy Workshops (EuroS&PW))
The security of Industrial Control Systems is relevant both for reliable production system operations and for high-quality throughput in terms of manufactured products. Security measures are designed, operated and maintained by different roles along product and production system lifecycles. Defense-in-Depth as a paradigm builds upon the assumption that breaches are unavoidable. The paper at hand provides an analysis of roles, corresponding Human Factors and their relevance for data theft and sabotage attacks. The resulting taxonomy is reflected by an example related to Additive Manufacturing. The results assist in both designing and redesigning Industrial Control System as part of an entire production system so that Defense-in-Depth with regard to Human Factors is built in by design.
Keywords: Defense-in-Depth; Human Factors; Production Engineering; Product Design; Systems Engineering

Extremwettersituationen in alpinen Gebieten: Management kritischer Situationen in Echtzeit bei extremen und komplexen Daten - Pottebaum, Jens; Rechberger, Christina; Hieb, Michael; Gräßler, Iris; Resch, Christian (Tagungsband der Fachtagung Katastrophenforschung 2023)
Extremwettersituationen sind durch die Kombination von globalen und lokalen Wirkzusammenhän-gen gekennzeichnet. In der Gefahrenanalyse und -reaktion ist deshalb der Umgang mit extremen Daten erforderlich, die von heterogenen Datenquellen bezogen und mittels unterschiedlicher Ver-fahren bis hin zum maschinellen Lernen ausgewertet werden. Die Visualisierung dieser zwangsläufig unsicherheitsbehafteten Daten stellt eine Herausforderung dar. Diese wirkt umso bedeutsamer, je weniger Fachexpertise in Bereichen wie Meteorologie, Geologie oder Sensortechnik in einer Füh-rungs- oder Leitstelle eingebunden werden kann. Das Management kritischer Situationen in Echtzeit bei extremen und komplexen Daten muss daher auf einer Bewertung der Informationsqualität von extremen Daten beruhen. Diese Bewertung ist abhängig vom Anwendungskontext in unterschiedli-chen Führungs- und Assistenzstellen sowie der verfügbaren Infrastruktur mit Geräten zur Visualisie-rung, Schnittstellen von Wetterdiensten, Sensorsysteme und Rettungsrobotik. Im Beitrag wird der Ansatz des EU-Projekts CREXDATA in Bezug auf mögliche pluviale Hochwassersituationen in Inns-bruck vorgestellt. Grundlage bildet die Kategorisierung von extremen Daten, die Schnittstellen zu Datenquellen mit globalem und lokalem Bezug sowie Anwendungsfälle für die Visualisierung von Informationen. Es werden somit Grundlagen präsentiert, die in allen Formen von geobasierten Lage- und Führungsinformationssystemen zum Einsatz kommen können.

From Agile Strategic Foresight to Sustainable Mechatronic and Cyber-Physical Systems in Circular Economies - Gräßler, Iris; Pottebaum, Jens (Design Methodology for Future Products)

Evaluation Criteria in Product Idea Selection Decisions - Gräßler, Iris; Koch, Anna-Sophie (XXXIII Proceedings of the ISPIM Innovation Conference)
Within innovation management, choosing the best fitting product idea is the most important decision point. The future existence and success of the organization is depending on selected product ideas. To find the best fitting idea for an organization, it needs evaluation criteria representing the organizations mission Therefore, this study focuses on a holistic overview about evaluation criteria and on supporting organizations in the process to select its individual evaluation criteria. Based on a literature study, existing approaches regarding evaluation criteria in product idea selection are identified and a list of evaluation criteria is reworked. Using the list of evaluation criteria, a prioritization method is created. Within an interview with experts in innovation management, the method is discussed regarding usability and the level of assistance in product idea selection. The developed criteria can be used directly by innovation manager and industrial practitioners to evaluate potential product ideas.
Keywords: innovation management; evaluation criteria; idea selection; idea evaluation; meta-study

Proaktives Management von Anforderungsänderungen in der Entwicklung komplexer technischer Systeme - Oleff, Christian
Anforderungsänderungen sind ein wesentlicher Grund für Ineffizienzen und Projektfehlschläge in der Entwicklung komplexer technischer Systeme. Proaktives Management von Anforderungsänderungen hat das Potenzial, den Umgang mit Anforderungsänderungen effizienter zu gestalten. Dafür ist ein systematischer Ansatz erforderlich, der eine ganzheitliche Bewertung und Handhabung des Änderungsrisikos im industriellen Entwicklungskontext ermöglicht. Im Rahmen dieser Dissertation wird mit der ProMaRC-Methodik ein neuartiger Ansatz für das proaktive Management von Anforderungsänderungen vorgestellt. Die Methodik wurde in enger Zusammenarbeit mit Industrieanwender:innen aus der Automobilindustrie entwickelt und anhand von fünf Fallstudien validiert. Mittels automatisierter Abhängigkeitsanalyse auf Grundlage künstlicher Intelligenz wird der Anwendungsaufwand gegenüber bestehenden Ansätzen reduziert. Die teilautomatisierte Bewertung und Handhabung der Änderungswahrscheinlichkeit und -auswirkung erfolgt anhand eines modifizierten PageRank-Algorithmus und umfasst erstmalig alle für die Risikoanalyse relevanten Einflussfaktoren. Die Validierung belegt, dass durch die ProMaRC-Methodik eine überzeugende Kombination aus praxistauglichem Anwendungsaufwand und Vollständigkeit der Analyse erzielt wird. Damit erschließt diese Dissertation das bisher kaum beachtete Forschungsfeld des proaktiven Managements von Anforderungsänderungen und fördert eine effizientere Produktentwicklung.

Systems Engineering - verstehen und industriell umsetzen - Gräßler, Iris; Oleff, Christian
Wie werden technische Systeme zeitgemäß entwickelt, die in Komplexität und Anspruch alles bisher Dagewesene übertreffen? Darauf gibt Systems Engineering Antworten. Bisherige Beschreibungen sind für den Maschinenbau aber oft schwer greifbar und zu unkonkret. Dieses Buch bricht den internationalen Stand der Wissenschaft auf das Wesentliche herunter und beschreibt praxisnah die Kernelemente des Systems Engineering. Eine konkrete Schritt-für-Schritt Anleitung ebnet den Weg für den erfolgreichen Transfer aus der klassischen Produktentwicklung hin zum Systems Engineering. Die Inhalte werden grafisch professionell und bewusst lebendig vermittelt. So wird nicht nur ein fundiertes Systems Engineering-Verständnis geschaffen, sondern auch die Basis für Kommunikation und Umsetzung im Unternehmen gelegt.

Supporting Business Model Generation with Augmented Reality - Gräßler, Iris; Grewe, Benedikt; Kramer, Hendrik (LUT Scientific and Expertise Publications)
Workshops on business model generation lead to collaborative work phases and discussions on business models. Therefore, tools such as the Business Model Canvas are used, typically filled with sticky notes. Generated content needs to be digitized in a time-consuming manual follow-up as part of the documentation and basis for a further use of the results in the company. In addition, there are challenges, such as decentralized work and digital workshop formats. Augmented Reality offers a way to reduce the digitization effort and enables decentralized work. In this research, the potentials of the use of AR technology in workshops on business model generation is investigated. Therefore, functions are implemented and evaluated in a demonstrator that reduces digitization effort and enable distributed work.
Keywords: business model generation; augmented reality; workshop; collaborative work; digitization; AR-supported workshop concept; immersive technologies; decentralized work; business model canvas

Szenario-Technik - Gräßler, Iris; Scholle, Philipp; Thiele, Henrik (Integrated Design Engineering. Ein interdisziplinäres Modell für die ganzheitliche Produktentwicklung, Kapitel: 20)

Responsibility Assignment in Systems Engineering - Gräßler, Iris; Thiele, Henrik; Grewe, Benedikt; Hieb, Michael (Proceedings of the Design Society)
Abstract Increasing system complexity can be controlled by using systems engineering processes. INCOSE defines processes with inputs and outputs (artifacts) for this purpose. Specific SE roles are used to organize the tasks of the processes within the company. In this work, the responsibilities for artifacts are evaluated by means of the RACI scheme and examined by a cluster analysis and discussed for a SE transformation project with a German automotive OEM. As a result of the study, the optimal composition for systems engineering teams is identified and the systems engineering roles are prioritized.
Keywords: systems engineering (SE); project management; model-based systems engineering (MBSE)

Automatisierte dezentrale Produktionssteuerung für cyber-physische Produktionssysteme mit digitaler Repräsentation der Beschäftigten - Pöhler, Alexander
In dieser Arbeit wird die Entwicklung einer dezentralen Produktionssteuerung mit digitaler Repräsentation zur Anwendung in cyber-physischen Produktionssystemen (CPPS) beschrieben. Die dezentrale Produktionssteuerung geschieht hierbei selbstorganisiert, da sie die Einlastung und Umplanung von Aufträgen sowie die Koordination zwischen den einzelnen Produktionselementen selbstständig übernimmt. Dies erlaubt die automatisierte Steuerung von CPPS. Dabei spielen die Beschäftigten in dieser Betrachtung eine wesentliche Rolle. Ihre Bedürfnisse und Wünsche werden von dem Steuerungssystem berücksichtigt. Dafür wurde das Konzept der digitalen Repräsentation von Beschäftigten entwickelt. Diese Repräsentation erlaubt den individuellen Eingriff von Beschäftigten bei Entscheidungen von dem Steuerungssystem. Das automatisierte dezentrale Steuerungssystem wurde in einer Laborumgebung, die zu einem CPPS umgebaut wurde, implementiert. Darauf basierend wurde eine zweistufige Validierung durchgeführt. Ein Teil der Validierung findet durch eine reale Umsetzung in einem Labor statt, bei der ein Vergleich zu dem vorher im Labor eingesetzten zentralen Produktionssteuerungssystem gezogen wird. Die zweite Validierung erfolgt mit Hilfe einer Simulationsumgebung. Dabei konnte die Implementierung der Selbstorganisation und eine Steigerung der Liefertreue der dezentralen Produktionssteuerung gegenüber heutzutage üblicherweise eingesetzten Verfahren nachgewiesen werden.

Information Model for Hybrid Prototyping in Design Reviews of Assembly Stations - Gräßler, Iris; Roesmann, Daniel; Hillebrand, Stefan; Pottebaum, Jens (Procedia CIRP ICME)
Keywords: General Medicine

Extrahierung von Anforderungen aus natürlich-sprachlichen Lastenheften: Was erschwert eine KI-basierte Extrahierung? - Gräßler, Iris; Preuß, Daniel; Pottebaum, Jens (Softwaretechnik-Trends)

Automated Requirement Dependency Analysis for Complex Technical Systems - Gräßler, Iris; Oleff, Christian; Hieb, Michael; Preuß, Daniel (Proceedings of the Design Society)
Abstract Requirements changes are a leading cause for project failures. Due to propagation effects, change management requires dependency analysis. Existing approaches have shortcomings regarding ability to process large requirement sets, availability of required data, differentiation of propagation behavior and consideration of higher order dependencies. This paper introduces a new method for advanced requirement dependency analysis based on machine learning. Evaluation proves applicability and high performance by means of a case example, 4 development projects and 3 workshops with industry experts.

Mensch-Tracking zur Identifizierung des Voranschreitens von Roboterunterstützten Rettungseinsätzen der Feuerwehr - Gräßler, I.; Roesmann, Daniel; Pottebaum, Jens; Corves, Burkhard; Mandischer, Nils; Gürtler, Marius (Tagungsband der VDI Mechatronik 2022)

Extended RFLP for complex technical systems - Gräßler, Iris; Wiechel, Dominik; Oleff, Christian

Literature study on the potential of Artificial Intelligence in Scenario-Technique - Gräßler, Iris; Tusek, Alena Marie; Thiele, Henrik; Preuß, Daniel; Grewe, Benedikt; Hieb, Michael (XXXIII ISPIM Innovation Conference Proceedings)

Efficient Extraction of Technical Requirements Applying Data Augmentation - Gräßler, Iris; Preuß, Daniel; Brandt, Lukas; Mohr, Michael (Proceedings of 8th IEEE International Symposium on Systems Engineering 2022)

Gestaltung einer Forschungsinfrastruktur für die Anwendung digitaler Werkzeuge in Cyber-Physischen Produktionssystemen - Gräßler, Iris; Hieb, Michael; Roesmann, Daniel (Automation 2022)

Proactive Management of Requirement Changes in the Development of Complex Technical Systems - Gräßler, Iris; Oleff, Christian; Preuß, Daniel (Applied Sciences)
Requirement changes and cascading effects of change propagation are major sources of inefficiencies in product development and increase the risk of project failure. Proactive change management of requirement changes yields the potential to handle such changes efficiently. A systematic approach is required for proactive change management to assess and reduce the risk of a requirement change with appropriate effort in industrial application. Within the paper at hand, a novel method for Proactive Management of Requirement Changes (ProMaRC) is presented. It is developed in close collaboration with industry experts and evaluated based on workshops, pilot users’ feedback, three industrial case studies from the automotive industry and five development projects from research. To limit the application effort, an automated approach for dependency analysis based on the machine learning technique BERT and semi-automated assessment of change likelihood and impact using a modified PageRank algorithm is developed. Applying the method, the risks of requirement changes are assessed systematically and reduced by means of proactive change measures. Evaluation shows high performance of dependency analysis and confirms the applicability and usefulness of the method. This contribution opens up the research space of proactive risk management for requirement changes which is currently almost unexploited. It enables more efficient product development.
Keywords: Fluid Flow and Transfer Processes; Computer Science Applications; Process Chemistry and Technology; General Engineering; Instrumentation; General Materials Science

Fortschrittskontrolle der Modellierung mechatronischer Produkte - Gräßler, Iris; Wiechel, Dominik; Thiele, Henrik (Tagungsband der Fachtagung VDI-Mechatronik)
Die Anforderungen an die Entwicklung mechatronischer Systeme sind seit der Erstfassung der VDI Richtlinie 2206 im Jahr 2004 stetig gestiegen. Nach einer umfassenden Überarbeitung ist 2021 die Richtline im Weißdruck neu veröffentlicht worden. Neben dem Systemdenken als gestärktes Kernelement des V-Modells und sechs Kontrollpunkten nur Gliederung der sachlogischen Aufgaben ist die durchgängig explizite „Modellierung und Analyse“ eine wesentliche Neuerung der Richtlinie. Da sich die Kontrollfragen nur auf den Entwicklungsprozess im Ganzen beziehen, wird durch die Betrachtung der Modellierung eines Batteriesystems aus einem Entwicklungsprojekt eines deutschen Automobilherstellers die folgende Forschungsfrage betrachtet: Welche spezifischen Kontrollfragen zu Fortschritt und Reifegrad der Modellierung eines Batteriesystems können aus den Kontrollpunkten des V-Modells (VDI 2206:2020) gefolgert werden? Als Ergebnis der Forschung liegen hinsichtlich der Modellierung eines spezifischen Systems detaillierte Kontrollfragen vor, die eine methodische Unterstützung für die modellbasierte Systementwicklung komplexer mechatronischer Systeme bieten. Zusätzlich ermöglichen sie der Projektleitung die Überprüfung des aktuellen Status der Entwicklung und sichern die Vollständigkeit des Systemmodells ab.

Approach to Sustainability-Based Assessment of Solution Alternatives in Early Stages of Product Engineering - Gräßler, Iris; Hesse, Philipp (Proceedings of the Design Society)
Sustainable product engineering is becoming increasingly important. This includes the development of environmentally friendly products and the design for recycling. In this paper a holistic method for the assessment of solution alternatives is presented, in which the stakeholder perspectives along the generic product lifecycle are taken into account. Finally, a new visualization is presented. By visualizing the results in the integrated sustainability triangle, decision-makers in product development can holistically assess the sustainability of the solution alternatives.
Keywords: sustainability; decision making; generic product lifecycle; design analysis; ecodesign

Model-Based Effect-Chain Analysis for Complex Systems - Gräßler, Iris; Wiechel, Dominik; Koch, Anna-Sophie; Preuß, Daniel; Oleff, Christian (Proceedings of the Design Society)
Abstract Effect chain modeling approaches are applied to model cause-effect relations and analyze affected elements and dependencies. In this paper a systematic literature research is conducted to derive main characteristics and limitations of existing approaches. Then, the Model-based Effect Chain Analysis (MECA) method is introduced. Evaluation proves applicability of the method by means of a case example. This is done in the context of a project with a German automotive company. In the project 66 workshops were conducted to model certification-compliant effect chains in accordance to the UN ECE 156.